Ethics in medical decision making: an intercultural outlook - A.V BERESTOVA (Utopía y Praxis Latinoamericana, 2019)
In the climate of globalization, the choice dilemma is complicated by ethical conflicts that exist in multicultural contexts. This article investigates the capacity criteria across cultures and the boundaries of delegating responsibility for the patient's health to other people. The attitude towards euthanasia was taken as a marker to trace differences. Statistical analysis of euthanasia acceptability in 2017 involved Western civilizations, according to Huntington. The analysis showed a high prevalence of euthanasia in the Netherlands (48%) and the lowest prevalence in the United States (2%) and Canada (2%). Religious beliefs have a direct effect on ethics in decision making.